Molecular techniques for sex identification of captive birds - Medania Purwaningrum; Herjuno Ari Nugroho; Machmud Asvan; Karyanti Karyanti; Bertha Alviyanto; Randy Kusuma; Aris Haryanto (Veterinary World, 2019)
Background and Aim: Many avian species are considered sexually monomorphic. In monomorphic bird species, especially in young birds, sex is difficult to identify based on an analysis of their external morphology. Accurate sex identification is essential for avian captive breeding and evolutionary studies. Methods with varying degrees of invasiveness such as vent sexing, laparoscopic surgery, steroid sexing, and chromosome inspection (karyotyping) are used for sex identification in monomorphic birds. This study aimed to assess the utility of a non-invasive molecular marker for gender identification in a variety of captive monomorphic birds, as a strategy for conservation.